Equality in financial access to healthcare in Cambodia from 2004 to 2014. Issue 8 (27th August 2018) - Fernandes Antunes, Adélio; Jacobs, Bart; de Groot, Richard; Thin, Kouland; Hanvoravongchai, Piya; Flessa, Steffen
Abstract: Since the end of its internal conflict in 1998, Cambodia has experienced tremendous developments in the social, economic and health sectors, with the government embarking on substantial reforms in health financing. Health equity funds that have improved access to public health services for poor people have gradually been extended to the entire country. Using the World Health Organization's methods for the analysis of healthcare expenditure and household survey data from the 2004, 2009 and 2014 Cambodian Socio-Economic Survey, we assessed trends in reported illness, utilization of healthcare services and associated financial burden on households. The impact of out-of-pocket expenditures for health on catastrophic health expenditures, poverty headcount and depth over the same 10-year period are presented, disaggregated by consumption quintile and place of residence (rural, urban and capital). At the aggregated national level, evolution of these indicators was very positive and correlates with a substantial increase in the capacity-to-pay of households, which reduced the average financial burden on households. However, over time inequalities grew between rural and urban areas. By 2014, the national incidence of catastrophic health expenditure was 4.9%, but four times more likely among rural households than their peers in the capital. For rural households with members seeking medical care, catastrophic health expenditure incidence was 12.3%. The impoverishment rate due to health spending among the lowest consumption quintile was 15.3%; the highest rate in this analysis. These findings suggest that economic and health sector developments have indeed benefited many Cambodian people. However, these gains mainly benefited urban residents; especially those in the capital city. We argue that more resources should be allocated to rural health services to address inequalities and healthcare-related financial hardship, which traps vulnerable people into poverty.